Galanin and neuropeptide Y interactions elicit antidepressant activity linked to neuronal precursor cells of the dentate gyrus in the ventral hippocampus - Borroto Escuela, Dasiel Óscar; Pita-Rodríguez, Mariana; Fores-Pons, Ramón; Barbancho-Fernández, Miguel Ángel; Fuxe, Kjell; Narváez-Peláez, Manuel (Wiley, 2021)
A need for new antidepressants is necessary since traditional antidepressants have several flaws. Neuropeptide Y(NPY) Y1 receptor (NPYY1R) and galanin (GAL) receptor 2 (GALR2) interact in several regions of the limbic system, including the hippocampus. The current study assesses the antidepressant effects induced by GALR2 and NPYY1R coactivation, together with the evaluation of cell proliferation through 5-Bromo-2'-deoxyuridine expression within the dentate gyrus of the ventral hippocampus (vDG). We employed in situ proximity ligation assay to manifest GALR2/NPYY1R heteroreceptor complexes. Additionally, the expression pattern of GALR2 and the activation of the extracellular-regulated kinases (ERK) pathway after GALR2 and NPYY1R costimulation in cell cultures were examined. GALR2 and NPYY1R coactivation resulted in sustained antidepressant behaviors in the FST after 24 h, linked to increased cell proliferation in the vDG. Moreover, an increased density of GALR2/NPYY1R heteroreceptor complexes was observed in vDG, on doublecortin-expressing neuroblasts. Recruitment of the GALR2 expression to the plasma membrane was observed upon the coactivation of GALR2 and NPYY1R in cell cultures, presumably associated to the enhanced effects on the activation of ERK pathway. GALR2 may promote the GALR2/NPYY1R heteroreceptor complexes formation in the ventral hippocampus. It may induce a transformation of cell proliferation toward a neuronal lineage by enhancement of ERK pathway. Thus, it may give the mechanism for the antidepressant behavior observed. These results may provide the basis for the development of heterobivalent agonist pharmacophores, targeting GALR2/NPYY1R heteromers, especially in the neuronal precursor cells of the dentate gyrus in the ventral hippocampus for the novel treatment of depression.
https://openpolicyfinder.jisc.ac.uk/id/publication/13864
Keywords: Neuropéptidos; Receptores de neurotransmisores; Depresión mental; Depression; Galanin; Neuropeptide Y; Neuropeptides; Receptor interaction